Does Continuous Wear of a Face Mask Affect Your Tear Film? - S. Gunaganti; M. Koduri; S. Mereddy (Oftalʹmologiâ, 2023)
Purpose. The continuous use of mask wear from pandemic induces instability in tear film due to the air blown up from the mask. The study’s objective was to assess the effect of type of mask wear and duration, including short-term wear of mask on TBUT.Design and methods. This was a cross-sectional, comparative study. A total of 90 (180 eyes) subjects (76 females) were involved in the study and were categorized into three groups, each comprising 30 subjects. Either the groups were given a surgical, cloth, or N95 masks to wear. Baseline TBUT was collected after 30 mins without mask wear; next TBUT was measured immediately after 1 min of mask wear and subsequently after every 30 mins for 3.5 hours among all the three groups. TBUT changes within the groups and between the groups were compared using Friedman ANOVA and the Kruskal Wallis test.Results. There was a significant decline in TBUT after 30 mins of mask wear only among surgical & cloth mask users and was stable in N95 wearers. There is no influence on TBUT for 1.5 hours among all the mask wearers. However, a subsequent continuous significant difference was evident from 2 hours among surgical and cloth mask users and at 3.5 hours within N95 users. N95 wearers have a higher TBUT, and surgical have the least TBUT.Conclusion. Surgical mask wears significantly influence tear film stability, followed by cloth mask wear because of air leak from nose wire. TBUT is minimally affected by N95 wear.